2006
DOI: 10.1192/bjp.188.2.165
|View full text |Cite|
|
Sign up to set email alerts
|

Psychological impact of stillbirth on fathers in the subsequent pregnancy and puerperium

Abstract: The vulnerability of fathers to psychological distress during the pregnancy after a stillbirth needs to be recognised.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
82
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(92 citation statements)
references
References 34 publications
(2 reference statements)
6
82
4
Order By: Relevance
“…H1 was supported, as mothers reported higher levels of PTSD across all symptom clusters and were assigned a probable PTSD diagnosis almost twice as often as fathers. This is in contrast to a study reporting similar PTSD levels in mothers and fathers in the first pregnancy following a stillbirth [8]. However, the results are in accordance with another study reporting significantly higher PTSD levels in mothers up to 1 year after the loss [3].…”
Section: Discussioncontrasting
confidence: 79%
See 2 more Smart Citations
“…H1 was supported, as mothers reported higher levels of PTSD across all symptom clusters and were assigned a probable PTSD diagnosis almost twice as often as fathers. This is in contrast to a study reporting similar PTSD levels in mothers and fathers in the first pregnancy following a stillbirth [8]. However, the results are in accordance with another study reporting significantly higher PTSD levels in mothers up to 1 year after the loss [3].…”
Section: Discussioncontrasting
confidence: 79%
“…Mothers generally experience most grief reactions with greater intensity and for a longer duration of time than fathers [1,[4][5][6]. Compared with controls, bereaved mothers report significantly higher levels of anxiety, depression, and PTSD and have higher mortality rates even long after the loss [7][8][9]. In contrast, differences in fathers are only found shortly after the loss or not at all [7,9].…”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation
“…Couples who experienced the death of a baby were significantly more likely to have one or both partners distressed, compared to non-bereaved couples (Armstrong and Hutti, 1998;de Montigny et al, 1999). Several studies have reported that father's expression of grief was less intense than that of mother's (Volker and Striegel, 1995;Badenhorst et al, 2006;Turton et al, 2006). A review done by Hughes and Riches (2003) stated that bereaved parents often experience a grief that is unexpectedly pervasive, intense and enduring.…”
Section: Introductionmentioning
confidence: 99%
“…Whether or not prevalence rates of depression are similar in men and women is under debate, as various studies find contradictory results [10][11][12][13][14]. A substantial amount of research has been carried out regarding postpartum depression in men, and a recent meta-analysis estimated the prevalence at 10.4 percent [15].…”
Section: Introductionmentioning
confidence: 99%